Evaluation of liver and kidney function in of pregnant women with chronic liver disease infected with toxoplasmosis in Misan Province - Mohammed R. Hassoon / Qahtan Adnan Rasheed / Mohammed Sh. Jebur ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Objective: Toxoplasmosis represents one of the most widespread zoonosis parasitic disease caused by Toxoplasma gondii parasite, which is an intracellular protozoan. This disease infects all warm-blooded animals, including humans. Aims of study: The current study aimed to assess the blood urea, creatinine, AST: aspartate aminotransferase; ALT: alanine aminotransferase and toxoplasmosis among pregnant women with chronic liver disease.Materials and methods: The study was carried out during the period from October 2022 to the beginning of February 2023 with total number (200) pregnant women who attended to various governmental hospitals in Maysan Province-Iraq with their ages ranged from (19-35) years. Results: The results showed 11(9.9 %) of women had positive IgM antibodies to toxoplasmosis, while 98 (49.5%) had positive IgG antibodies to toxoplasmosis. Co-infection was found in both T. gondii/HCV and T. gondii/ hepatitis B virus, (66.7%   and 51.9 %) respectively. Women with chronic liver disease showed a significant increase of liver enzymes: aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in pregnant with toxoplasmosis compared women with no toxoplasma infection. Also a significant increase of Creatinine was found in infected women compared with women with no toxoplasma gondii infection.